2021
DOI: 10.1007/s00259-021-05459-0
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of regional myocardial flow reserve derived from 13N-ammonia positron emission tomography in patients with suspected coronary artery disease

Abstract: Purpose To assess the prognostic value of regional quantitative myocardial flow measures as assessed by 13N-ammonia positron emission tomography (PET) myocardial perfusion imaging (MPI) in patients with suspected coronary artery disease (CAD). Methods We retrospectively included 150 consecutive patients with suspected CAD who underwent clinically indicated 13 N-ammonia PET-MPI and who did not undergo revascularization within 90 days of PET-MPI. The presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…4 In contrast, Von Felten et al recently demonstrated using 13 Nammonia, an independent prognostic value of regional MFR \ 2, being superior to global stress MBF and MFR. 26 In the current study, the first using the latest SiPM technology, whose characteristics might offer potential benefits for precise analysis, we found that severe regional per pixel MFC impairment is a powerful predictor of cardiovascular events, independent from traditional cardiovascular risk factors, but not from global perfusion parameters. Although the current study has inherent limitations which could limit the scope of the results, these data support a close relationship between global and regional perfusion.…”
Section: Discussionmentioning
confidence: 56%
“…4 In contrast, Von Felten et al recently demonstrated using 13 Nammonia, an independent prognostic value of regional MFR \ 2, being superior to global stress MBF and MFR. 26 In the current study, the first using the latest SiPM technology, whose characteristics might offer potential benefits for precise analysis, we found that severe regional per pixel MFC impairment is a powerful predictor of cardiovascular events, independent from traditional cardiovascular risk factors, but not from global perfusion parameters. Although the current study has inherent limitations which could limit the scope of the results, these data support a close relationship between global and regional perfusion.…”
Section: Discussionmentioning
confidence: 56%
“…Harjulahti et al found similar results using also [ 15 O]water PET (4). In contrast, Von Felten et al recently demonstrated using 13 N-ammonia, an independent prognostic value of regional MFR < 2, being superior to global stress MBF and MFR (24). In this study the authors emphasized several methodological differences for regional measurements between them: (i) a decrease in at least two adjacent segments, (ii) Bom et al: continuous variables computed as the average MFR values from the two adjacent segments with the lowest values, and (iii) Harjulahti et al: a single segment with stress MBF lower than 2.3 ml/g/min.…”
Section: Discussionmentioning
confidence: 86%
“…The quantification of absolute MBF and MFR by PET as markers of coronary vascular function provides an incremental value compared to clinical and perfusion data for both diagnostic and prognostic purposes in patients with suspected or known CAD [ 21 23 ]. Previous studies pointed up on prognostic value of MFR [ 24 27 ], demonstrating that the coronary vasodilator dysfunction is a powerful and independent correlate of cardiac mortality and provides significant incremental risk stratification [ 28 30 ]. The presence of reduced cardiac vascular function was associated with an increased risk of cardiac death even in the presence of normal scans by semi-quantitative visual analysis and independently of other risk factors [ 31 34 ].…”
Section: Discussionmentioning
confidence: 99%